PENGARUH COMPETITIVE ENVIRONMENT DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA ORGANISASI : STRATEGI ORGANISASI SEBAGAI VARIABEL MODERATING - Linda Hetri; Kirmizi Kirmizi; Desmiyawati Desmiyawati (Jurnal Ekonomi, 2015)
This study intends to give the empirical evidence on interaction effect of information management accounting system with organization strategy, competitive environment on organization performance. Organization strategy were used in this studyas moderating variable. Firts hypothesis and third hypothesis did’nt use moderating variable, second hypothesis and fourth hypothesis used organization strategy.Questionnaires were distributed to 103 manufacturing companies in Riau and Kep. Riau with purposive sampling method. The responses from middle managers and general manager, were analysed using Multiple Regression Analysis (MRA). The result support the hypothesis that management accounting system information influence on organization performance. Furthermore, the interaction effect of management accounting system information withorganization strategy on organization performance are not significant. Competitive environment influence on organization performance and organization strategy is moderat the relationship competitive environment and organization performance